2005
DOI: 10.1111/j.1471-6402.2005.00238.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluations of Sexy Women In Low- and High-Status Jobs

Abstract: We hypothesized that women who dress in a sexy versus business‐like manner evoke negative emotions and perceptions of lesser competence if employed in high‐ (but not low‐) status jobs. Male and female undergraduates evaluated a videotaped female target whose physical attractiveness was held constant, but who was (a) dressed in sexy or business‐like attire and (b) allegedly either a manager or a receptionist. Participants exhibited more negative affect toward the sexily attired manager and rated her as less com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
140
1
13

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(163 citation statements)
references
References 17 publications
9
140
1
13
Order By: Relevance
“…3 Although there were too few males to meaningfully examine interactions by gender, prior research has found no gender differences (e.g., Chiao et al, 2008;Glick et al, 2005). Further, controlling for participants' gender did not change the results.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…3 Although there were too few males to meaningfully examine interactions by gender, prior research has found no gender differences (e.g., Chiao et al, 2008;Glick et al, 2005). Further, controlling for participants' gender did not change the results.…”
Section: Discussionmentioning
confidence: 68%
“…Rudman and Borgida (1995) did, however, find that males rated a woman as less competent following exposure to sexualized images of other women. Also, Glick, Larsen, Johnson, and Branstiter (2005) manipulated a woman's attire so that she was dressed provocatively (and thus, likely to draw attention to her appearance) or not. When she was dressed provocatively, both men and women perceived her as less competent, but only when she was purportedly in a high status occupation (which of course, Vice President of the United States would be).…”
Section: Perceptions Of Competencementioning
confidence: 99%
“…The same paradigm has been modified and used by many researchers. Most recently Glick et al (2005), used a film as the stimulus. This was not considered appropriate for the present study, for when examining the Glick research, it is evident that study providing too much visual stimulus has the effect of concentrating the perceptions of those taking part on characteristics such as clothing.…”
Section: Methodmentioning
confidence: 99%
“…Glick et al (2005) found that as compared to a female receptionist, a female manager who emphasized her sexiness evoked less positive emotions, less job competence, and less intelligence. Subsequently, Gurung and Chrouser (2007) found that women wearing sexually stimulating attire were often seen as unintelligent and incapable.…”
Section: Reactions To Women Wearing Sexy Dressmentioning
confidence: 99%